2018
DOI: 10.7717/peerj.5809
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic differentiation of adipose-derived mesenchymal stem cells induced by L-ascorbic acid and platelet rich plasma on silk fibroin scaffold

Abstract: Articular cartilage is an avascular tissue with limited regenerative property. Therefore, a defect or trauma in articular cartilage due to disease or accident can lead to progressive tissue deterioration. Cartilage tissue engineering, by replacing defective cartilage tissue, is a method for repairing such a problem. In this research, three main aspects—cell, biomaterial scaffold, and bioactive factors—that support tissue engineering study were optimized. Adipose-derived mesenchymal stem cells (ADSC) that becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 35 publications
(39 reference statements)
1
37
0
Order By: Relevance
“…Overall, cell viability was slightly decreased from day 1 to day 5 and then increased steadily from day 7 until day 14. Initial decrease of cell viability of cells grown on silk scaffold was also observed on Antheraea mylitta silk fibroin scaffold 14 and B.mori silk fibroin scaffold 16,36 . This result was likely caused by cell adaptation and migration on the porous structure of the scaffold 37 .…”
Section: Scaffold Composition Optimization For Cell Proliferation Thmentioning
confidence: 70%
See 2 more Smart Citations
“…Overall, cell viability was slightly decreased from day 1 to day 5 and then increased steadily from day 7 until day 14. Initial decrease of cell viability of cells grown on silk scaffold was also observed on Antheraea mylitta silk fibroin scaffold 14 and B.mori silk fibroin scaffold 16,36 . This result was likely caused by cell adaptation and migration on the porous structure of the scaffold 37 .…”
Section: Scaffold Composition Optimization For Cell Proliferation Thmentioning
confidence: 70%
“…The overall pore size formed on scaffold was between the range of NaCl particles used (400-570 μm). Several studies have reported that scaffold with larger pore size; 370-400 μm 27 , 400-500 μm 16,28 were able to support MSCs chondrogenesis better than smaller pore size, mainly due to higher permeability of gases and nutrition from culture medium 29 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, proteoglycan production also increased. 49 Parathyroid hormone-related protein (PTHrP) has been reported to perform fundamental roles in cartilage homeostasis, maintaining the chondrocyte phenotype. The effect of PTHrP on MSCs mainly depends on the pattern of application.…”
Section: Other Chondrogenic Proteinsmentioning
confidence: 99%
“…In future work, we propose the use of CMs as possible bioactive agent carriers and cell transporters. With extensive work performed looking into adipose-derived mesenchymal stem cells (ADSC) on chondrocyte cells and on the differentiation into chondrocyte cells we feel that CMs are uniquely suited as an injectable transporter for ADSCs into osteoarthritc tissues due to their injectable size and their affinity core cellular adherence(Barlian, Judawisastra, Alfarafisa, Wibowo, & Rosadi, 2018;Manferdini et al, 2013;Zhou et al, 2019). We would like to look at the integration of CMs and ADSCs in a traditional impeller bioreactor and look into the effect of CM-ADSCs on osteoarthritic chondrocyte cells or CM-differentiated ADSCs into chondrocyte cells on osteoarthric articular cartilage.…”
mentioning
confidence: 99%